Evaluasi Program Digitalisasi Sekolah Penggerak di SDN 3 Terusan Karya Kabupaten Kapuas - Dewi Siti Rahmah (Journal on Education, 2023)
This research uses a type of evaluation research with the CIPP model. The results of the context stage study show that the informants' understanding of the School Digitalization program Number 371 of the Ministry of Education and Culture in 2021 is not perfect. This can be seen from 17 informants, 1 person does not understand, 7 people understand and 4 people understand quite well. There were only 5 informants who stated they understood. Likewise, 6 people and 7 people did not understand the aim of the driving school program. In fact, how can a program be implemented well if the rationale and objectives of the program are not well understood. At the input stage, based on survey data analysis, the three components used as indicators in this research are school motivation, commitment to implementing school digitalization in the Good category. In evaluating input components of facilities and infrastructure, namely. chromebook, internet and other facilities (electricity), fulfilled 100%. As a result of tracing the process stages, it is known that information regarding the operational components of the mechanism, activity schedule and related parties is in the Good category. Based on the results of research conducted at the production stage, information was obtained that from 17 informants consisting of school principals, 8 teachers and 8 students for general evaluation, namely context, input, process and product, if calculated, the average score was 66. 02% in the Good category.